(untitled) (Research, Society and Development, 2020)
Objective: to analyze an occurrence of phlebitis associated with peripheral venous catheterization in hospitalized patients and to identify its relationship with age and catheter caliber. Methodology: Quantitative cohort study, developed in a clinical ward of a Large University Hospital in the State of Rio de Janeiro, Brazil. A sample was sequenced and composed of 27 patients using a peripheral intravenous device. Data collection took place from March to May 2019, using a form that includes changes in the characterization of lesions and venous catheterization. A relative risk was performed or considered for variables of interest: age and caliber of the catheters. Results: There was a predominance of grade I, with 75% of cases. The elderly are at a higher relative risk of developing phlebitis when compared to adults. Calibers 18 and 20 have a higher relative risk of developing phlebitis compared to 22 and 24. Conclusion: The occurrence of phlebitis is higher in the elderly, and when punishment occurs with calibers 18 and 20. The study is expected to contribute to a practice clinical nursing professionals, with no sense of decreasing the use of gauges 18 and 20, and following protocols to prevent phlebitis in the elderly.